Impact of the Nordic hamstring and hip extension exercises on hamstring architecture and morphology: implications for injury prevention. Issue 5 (22nd September 2016) - Bourne, Matthew N; Duhig, Steven J; Timmins, Ryan G; Williams, Morgan D; Opar, David A; Al Najjar, Aiman; Kerr, Graham K; Shield, Anthony J
Abstract : Background: The architectural and morphological adaptations of the hamstrings in response to training with different exercises have not been explored. Purpose: To evaluate changes in biceps femoris long head (BFLH ) fascicle length and hamstring muscle size following 10-weeks of Nordic hamstring exercise (NHE) or hip extension (HE) training. Methods: 30 recreationally active male athletes (age, 22.0±3.6 years; height, 180.4±7 cm; weight, 80.8±11.1 kg) were allocated to 1 of 3 groups: (1) HE training (n=10), NHE training (n=10), or no training (control, CON) (n=10). BFLH fascicle length was assessed before, during (Week 5) and after the intervention with a two-dimensional ultrasound. Hamstring muscle size was determined before and after training via MRI. Results: Compared with baseline, BFLH fascicles were lengthened in the NHE and HE groups at mid-training (d=1.12–1.39, p<0.001) and post-training (d=1.77–2.17, p<0.001) and these changes did not differ significantly between exercises (d=0.49–0.80, p=0.279–0.976). BFLH volume increased more for the HE than the NHE (d=1.03, p=0.037) and CON (d=2.24, p<0.001) groups. Compared with the CON group, both exercises induced significant increases in semitendinosus volume (d=2.16–2.50, ≤0.002) and these increases were not significantly different (d=0.69, p=0.239). Conclusion: NHE and HE training both stimulate significant increases in BFLH fascicle length; however, HE training may be more effective for promoting hypertrophy in the BFLH .